Prospects, challenges and current status of RNAi through insect feeding. Issue 1 (17th September 2019) - Kunte, Nitish; McGraw, Erin; Bell, Sydney; Held, David; Avila, Luz‐Adriana
Abstract: RNA interference is a phenomenon in which the introduction of double‐stranded RNA (dsRNA) into cells triggers the degradation of the complementary messenger RNA in a sequence‐specific manner. Suppressing expression of vital genes could lead to insect death, therefore this technology has been considered as a potential strategy for insect pest control. There are three main routes of dsRNA administration into insects: (i) injections to the hemolymph, (ii) topical, and (iii) feeding. In this review, we focus on dsRNA administration through feeding. We summarize novel strategies that have been developed to improve the efficacy of this method, such as the use of nano‐based formulations, engineered microorganisms, and transgenic plants. We also expose the hurdles that have to be overcome in order to use this technique as a reliable pest management method. © 2019 Society of Chemical Industry Abstract : Administration of dsRNA holds great potential as a pest management technique. This review discusses dsRNA mode of action, delivery mechanisms, and limitations of this approach.